2022
DOI: 10.1002/ejic.202200288
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Direct C−H Olefination of Polyfluoroarenes with Alkenyl Tosylates

Abstract: The first general examples of palladium‐catalyzed direct C−H olefination of polyfluoroarenes using alkenyl tosylates as electrophilic coupling partners are presented. By employing the Pd/L1 catalyst system (L1=N‐methyl‐2‐(2’,4’‐dimethoxyphenyl)‐3‐dicyclohexylphosphinoindole), the olefinated polyfluoroarenes can be obtained in good‐to‐excellent yields. Good structural and functional compatibility are also exhibited. In particular, the steric demanding and heterocyclic alkenyl tosylates react smoothly under this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…50 Very recently, the first direct C−H olefination of polyfluoroarenes with alkenyl tosylates was reported using the [(BPA)PdOMs] 2 /L6 catalyst system with PivOH as an additive (Scheme 15C). 51 Initial ligand screening revealed that WK-phos with two orthomethoxy groups surprisingly suppressed the reaction when compared with structurally similar PCy 2 -Andole-phos (16 vs 24% yield, respectively). It is believed that the larger proximal steric hindrance of WK-phos was responsible for the decreased product yield.…”
Section: Direct C−h Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Very recently, the first direct C−H olefination of polyfluoroarenes with alkenyl tosylates was reported using the [(BPA)PdOMs] 2 /L6 catalyst system with PivOH as an additive (Scheme 15C). 51 Initial ligand screening revealed that WK-phos with two orthomethoxy groups surprisingly suppressed the reaction when compared with structurally similar PCy 2 -Andole-phos (16 vs 24% yield, respectively). It is believed that the larger proximal steric hindrance of WK-phos was responsible for the decreased product yield.…”
Section: Direct C−h Functionalizationmentioning
confidence: 99%
“…Later, the arylation of polyfluoroarenes with sterically congested aryl chlorides was achieved using a C3-type indolylphosphine ligand containing the −PPh 2 moiety (Scheme B) . Very recently, the first direct C–H olefination of polyfluoroarenes with alkenyl tosylates was reported using the [(BPA)­PdOMs] 2 / L6 catalyst system with PivOH as an additive (Scheme C) . Initial ligand screening revealed that WK-phos with two ortho -methoxy groups surprisingly suppressed the reaction when compared with structurally similar PCy 2 -Andole-phos (16 vs 24% yield, respectively).…”
Section: C3-type Monophosphorus Ligandsmentioning
confidence: 99%